Who trusts wind farms? A vignette study on tailoring trust-building strategies for inclusive renewable energy transitions - Yalaz, Evren; Zamorano, Mariano Martín; Maitland, Emily; Gurzawska, Agata; Szüdi, Gábor; Bartar, Pamela (Frontiers in Climate, 2025)
IntroductionClimate governance is increasingly contested, with public acceptance of renewable energy projects such as wind farms often facing resistance. This study explores how different trust-building strategies, including science communication, co-creation, benefit sharing, and social media, affect public perceptions of wind energy across diverse socio-demographic groups in four European countries (Austria, Cyprus, Greece, and Spain).MethodsDrawing on an experimental vignette-based survey developed within the EU-funded VERITY project, we assess the impact of these strategies on two contrasting demographic groups: Group 1 (young, urban, university-educated) and Group 2 (older, rural, without a university degree).ResultsOur findings reveal significant variations in trust and engagement, with Group 1 generally exhibiting more positive attitudes toward wind energy (mean score: 0.49), while Group 2 was neutral or slightly negative (−0.01). Benefit sharing emerged as the most universally effective strategy, improving perceptions across all groups, particularly among sceptical male respondents. Science communication was most effective among women, especially in Group 1, while social media showed minimal or negative impact.DiscussionThe study highlights the importance of tailoring trust-building strategies to different demographic contexts, emphasizing that a one-size-fits-all approach is inadequate for inclusive climate governance. These findings offer actionable insights for policymakers seeking to enhance public trust in renewable energy transitions, aligning local engagement strategies with broader climate diplomacy.